Diagnostic performance of traditional radiographic indices in detection of carpal collapse in Kienböck's disease. (July 2023) - Luitjens, Johanna; Goller, Sophia Samira; Schmitt, Rainer; Erber, Bernd; Van Schoonhoven, Jörg; Hesse, Nina
Correctly identifying carpal collapse is important for adequate treatment of Kienböck's disease. This study aimed to assess the accuracy of traditional radiographic indices in detecting carpal collapse to differentiate between Lichtman stages IIIa and IIIb. In 301 patients, carpal height ratio, revised carpal height ratio, Ståhl index and radioscaphoid angle were measured on plain radiographs by two blinded observers. As a reference standard, Lichtman stages were determined by an expert radiologist using CT and MR imaging. The interobserver agreement was excellent. In the differentiation between Lichtman stages IIIa and IIIb, measurements of indices showed moderate to good sensitivity (0.60–0.95) and low specificity (0.09–0.69) using normal cut-off values from the literature, while receiver operating curve analysis revealed poor area under the curve (58–66%). Traditional radiographic indices showed poor diagnostic performance in detecting carpal collapse in Kienböck's disease and did not reach sufficient accuracy in the differentiation between Lichtman stages IIIa and IIIb. Level of evidence: III